Vehicle tyres and road accidents - Eyad Masad (14153484) (2015)
A research team from Texas A&M University at Qatar (TAMUQ) and Texas A&M Transportation Institute (TTI) conducted during the past three years a study that focused on traffic safety situation in Qatar, tyre properties, and the influence of tyre properties on driving safety. The presentation will compare and contrast the specifications of the Gulf Standardization Organization (GSO) and other specifications used in Europe and United States. Consequently, the presentation will discuss recommendation for changes in GSO tyre specifications in order to better reflect climatic conditions in the region. One of the road safety issues in Qatar is the routine use of some drivers of off-road tyres on paved roads. The research team conducted comprehensive testing of off-road tyres and standard tyres that are used in a typical large SUV. In addition, the team developed computer models and conducted finite element analysis to simulate the driving and manoeuvring conditions of the different types of tyres. The experimental measurements and computer simulations revealed valuable information about performance of off-road tyres and risks associated of using them on roads in Qatar. The results will be very useful for the policy makers and the driving public regarding the development of regulations that control the use of off-road tyres. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.87